GENETIC ANALYSIS OF REPRODUCTIVE TRAITS IN BALI CATTLE MAINTAINED ON RANGE UNDER ARTIFICIALLY AND NATURALLY BRED - A. Gunawan; R. Sari; Y. Parwoto (Diponegoro University, 2011)
The aim of this study was to evaluate genetic analysis including heritability and further phenotypicand genetic trends of reproductive traits in Bali cattle. Reproductive traits studied were age at firstcalving (AFC), calving interval (CI) and pregnancy rate (PR). Data of reproductive traits were collectedfrom Breeding Centre of Bali Cattle, Denpasar-Bali at the year period of 2000-2007. To evaluate thegenetic analysis, heritability were estimated using the Mixed Model Least Squares and MaximumLikelihood procedure. The phenotypic and genetic trends were calculated using regression equation.Estimation of heritability for AFC, CI and PR were 0.22, 0.41 and 0.40, respectively. The phenotypictrend of AFC, CI and PR decreased at an average rate of 1.70 month, 10.4 days and 0.75% per year,respectively. The same pattern was showed for genetic trends for AFC, CI and PR decreased at 0.38month, 4.25 days and 0.30% per year respectively in the same period. The heritability of reproductiontraits in Bali cattle were considered as moderate to high (0.22-0.41) which means that the selectionprogram will be more effective and efficient in improving the genetic merits in Bali cattle.